CO2-producing polymer micelles. (October 2015) - Lee, Hoyoung; Lee, Jaewon; Park, Jaeyoung; Kwon, Taewook; Hong, Seunggweon; Won, You-Yeon
Abstract: Poly(propylene carbonate) (PPC) is a plastic material that can be mass produced from naturally abundant carbon dioxide. This polymer is also known to decompose back to CO2 when heated above about 200 °C. Here we report that the CO2 -generation temperature of PPC can be reduced down to the 40–80 °C range in aqueous environment by using a photoacid generator (PAG) as the catalyst for activating the random scission reaction of PPC. We also investigated the thermal degradation of a PPC-based amphiphilic block copolymer, poly(poly(ethylene glycol) methyl ether methacrylate)-poly(propylene carbonate)-poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMA-PPC-PPEGMA). These triblock copolymers form stable small-sized (<200 nm) micelles in water. We found evidence that with the aid of added PAG these micelles can degrade under mild heating conditions (<80 °C), similarly to what is expected from PPC homopolymer experiments. The combined results suggest that PPC-based amphiphilic block copolymers might be of interest for applications in ultrasound contrast. Graphical abstract: